La descentralización en la gestión financiera de los Gobiernos Autónomos Descentralizados Provinciales en el Ecuador - Cifuentes García, Luis Antonio (2014)
This research is the study of the basic guidelines of decentralization models in place in the Constitutions of the Republic of Ecuador in the years 1979.1998 and 2008. Approaches of decentralization of the last charter is developed, and then continue with the analysis of financial management of Government Autonomous Decentralized Provincials in Ecuador. In order to obtain the results of the fiscal years 2000 to 2012 showing the reality of subnational finances GAD provincial. Finally strategies for improving their fiscal capacity arises.